Periodontal tissue response to coverage of root cavities restored with resin materials: A histomorphometric study in dogs - Martins, Thiago M.; Bosco, Álvaro Francisco [UNESP]; Nobrega, Fernando J. O.; Nagata, Maria José Hitomi [UNESP]; Garcia, Valdir Gouveia [UNESP]; Fucini, Stephen E. (Amer Acad Periodontology, 2007)
Background: the purpose of this study was to histomorphometrically evaluate the response of periodontal tissues covering Class V resin restorations in dogs.Methods: After raising a mucoperiosteal flap, bony defects measuring 5 x 5 mm were created on the buccal aspect of the canines of five dogs followed by cavity preparations on the root surface measuring 3 x 3 x 1 mm. Before repositioning the flap to cover the bone defect, the cavities were restored with composite resin (CR) or resin-modified glass ionomer cement (RMGIC) or were left unrestored as control (C). The dogs were euthanized 90 days after surgery. Specimens comprising the tooth and periodontal tissues were removed, processed routinely, cut into longitudinal serial sections in the bucco-lingual direction, and stained with hematoxylin and eosin (H&E) or Masson's trichrome. The most central sections were selected for histomorphometric analysis.Results: Histomorphometric analysis revealed apical migration of epithelial tissue onto the restorative materials (RMGIC and CR). The C group presented significantly longer connective tissue attachment (P < 0.05) than the RMGIC and CR groups and significantly higher bone regeneration (P < 0.05) compared to the RMGIC group. Histologically, the cervical third (CT) of all groups had the most marked chronic inflammatory infiltrate.Conclusions: Within the limits of this study, it can be concluded that the restorative materials used exhibit biocompatibility; however, both materials interfered with the development of new bone and the connective tissue attachment process.
Keywords: animals; dental materials; healing; regeneration